Investigating the Effects of High Intensity Resistance Training on Physical Fitness of University Male Football Players - Yasmeen Tabassum; Sofia Amjad; Badar Mohy ud Din (The Sky, 2023)
High intensity resistance training (HIRT) can enhance strength, power, speed, agility, endurance and reduce injury risk in football players contributing to improved performance on the field. The purpose of this study was to determine eight-week high intensity resistance training (HIRT) intervention affected the physical fitness of male university football players. A randomized controlled design was adopted for the study and (n=24) football players between the ages of 19 and 25 took part. Before and during the intervention, which included three weekly training sessions, the participants were evaluated. The Yo Yo intermittent recovery test level 1 (YYIRT1), the 30 m sprint time (ST), the running based anaerobic sprint test (RAST) and the change of direction time (COD) were among the physical fitness tests. Following the eight week HIRT intervention, all experimental group variables revealed significant changes between pre- and post-tests.